Mayhem /3 - Salane, Jeffrey (Scholastic Press, 2016)
M Freeman has been through the Lawless School for criminal masterminds and the Fulbright Academy for extreme law enforcement, but her memory has been erased and she thinks she is a normal middle school student--but when a hitman from Lawless targets her, everything comes back, and she goes on the run with the help of the Ronins, a ragtag group made up of expelled students of both schools who have their own agenda.